Effectiveness of square stepping exercise among subjects with Parkinson's disease: A pilot Randomised Controlled Trial - Hariharasudhan Ravichandran; Balamurugan Janakiraman; Asmare Yitayeh; Subramanian Sundaram; Berihu Fisseha (Journal of Geriatric Mental Health, 2017)
Background: Parkinson's disease is a movement disorder that seriously affects body balance and gait; therefore, increases the risk of fall and related complications. Freezing of gait and postural instability are disabling symptoms, which compromises motor independence among Parkinson's disease patients. Aims and Objectives: The purpose of this study analyses the effects of square-stepping exercise (SSE) among Parkinson's disease patients in terms of improving balance and reducing fall risk. Materials and Methods: This is a pilot randomized controlled study, in which thirty male and female Parkinson's disease patients between 60 and 70 years of age were selected by simple random sampling method and randomly divided into SSE group (N-15) and conventional physiotherapy (CPT) group (N-15). Interventions were provided for 4 weeks. Baseline and posttest outcomes were measured using the Berg balance scale (BBS) and timed up and go test (TUG). Results: Statistical measures of mean, standard deviation, and t-test were performed using SPSS 21. SSE exhibited statistical significant improvement in BBS (P < 0.05) and TUG (P < 0.0001) compared to CPT group. Conclusion: SSE is more effective in improving balance and gait in Parkinson's disease. Although further studies with larger samples are required, the result of this study implies that SSE could be used as a mean of rehabilitation in Parkinson's disease.